Open‐circuit voltage, fill factor, and heterojunction band offset in semiconductor diode solar cells - Jizheng Wang (EcoMat, 2022)
Abstract Semiconductor photovoltaics have been investigated for many years, and various materials and device architectures have been developed aiming for low cost and high efficiency. Despite the critical advances in the field, there are confusions in understanding such diode based solar cells, especially on open‐circuit voltage and fill factor. This review intends to provide a succinct summary and interpretation for the core elements that are related to a solar cell device. First, the fundamental concepts of PN junction and diode solar cell are introduced. Second, Fermi and quasi‐Fermi levels are described, followed by understanding open‐circuit voltage and fill factor. Thirdly, the effects of heterojunction band offset are discussed. In the end, a brief conclusion is presented.